Acumulación de NPK por el girasol (Helianthus annuus L.) en un Mollisol del Valle del Cauca - Ortiz R. Gloria; Bastidas R. Gilberto (Acta Agronómica)
A field experiment was conducted to determine macronutrient concentration and amount of NPK absorbed by the different parts of the sunflower plant. The soil used was of the Palmira Serie (PL) classified as Pachic Haplustol of clay-loam texture, pH 6.4, 3.0% O.M., 63.9 ppm of P and 0.43 meq of K/100g of soil. The comercial hybrid DO- 664 was used, leaf, stem, bud, capitulum and seed samples wer taken 20, 40, 60 and 80 days post-emergence, chemicaly analized and N, P, K concentration determined. Results indicated more nitrogen concentration (3.19%) in leaves and potassium (5.4%) in the stems 40 days after emergence, while phosphorus (0.96%) was greatest in seed at 80 days. The order of absortion of the elements at 80 days in kg/ha was: K, 166.2; N, 69.2 and P, 16.7. This indicates that N and P fertilization should be fractionated up to day 40, while for K up to day 60. El estudio se realizó en un suelo de la serie Palmira (PL), clasificado como Pachic Haplustol, de textura francoarcillosa, pH 6.4, 3.0% de materia orgánica, 63.9 ppm de P y 0.43 meq de K/l00 g de suelo. Se utilizó el híbrido comercial DO-664 adelantando muestreos de hojas, tallos, botones, capítulos y semillas a los 20, 40, 60 Y 80 días después de la emergencia, analizándose químicamente y determinándose la concentración de N, P y K. Los resultados indicaron mayor concentración de nitrógeno (3.19%) en hojas y de potasio (5.4%) en tallos a los 40 días de emergencia, mientras que el fósforo (0.96%) fué en la semilla a los 80 días. La secuencia de absorción de elementos a los 80 días en kg/ha fue de 166.2 para potasio, 69.2 para nitrógeno y 16.7 para fósforo, indicando que para fertilizar con N y P se debe fraccionar el producto hasta los 40 días, mientras que para K hasta los 60 días.